READING STRATEGY IN FOCUS: NAVIGATING THE MEANING-MAKING PROCESSES IN READING MULTIMODAL TEXT - Nurviyani, Vina (University of Kuningan, 2024)
Indonesian EFL learners’ trouble comprehending multimodal texts was the main reason for this research. This study highlighted the reading strategy use in meaning reconstruction processes of multimodal reading. In this case, the meaning reconstruction process focused on the thinking processes of readers (EFL learners). This study applied a qualitative design (multiple case study) involving three readers studying at a private university in Indonesia. The triangulation data gained through verbal reports, non-participant observations, and interviews were analysed qualitatively. The findings show that all readers read the text while verbalizing their thoughts during the meaning reconstruction processes of the multimodal text. In the process, they segmented their verbal reports into many thought units. Each reader differently processed the thought units’ meanings through integrated reading strategies (i.e., monitoring comprehension, activating and connecting to background knowledge, questioning, inferring and visualizing meanings, determining the importance of text, summarizing and synthesizing). The use of the simultaneous integrated reading strategies is reflected in three stages of the meaning reconstruction process of reading print-based multimodal text, i.e., 1) Preparation, 2) Synchronization, and 3) Interpretation of the meaning. The complete meaning of each thought unit is reconstructed as a reader is able to implement the integrated reading strategies to find out the congruence of the multimodal information or knowledge of all reading elements (i.e., the reader’s prior knowledge, information of text, and context). Thus, reading strategies are crucial tools for reconstructing meanings of multimodal text.